2013
DOI: 10.1093/cid/cit745
|View full text |Cite|
|
Sign up to set email alerts
|

Statins and the Risk of Herpes Zoster: A Population-Based Cohort Study

Abstract: Statins have immunomodulating properties that may increase the risk of varicella-zoster virus reactivation. We found that older patients treated with statins were at an increased risk of developing herpes zoster relative to individuals who were not prescribed to these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…A recent report showed that older persons treated with statins had an increased risk of herpes zoster infections compared to those not treated with statins. 26 Statins have been shown to inhibit inflammatory chemokine expression, leukocyte migration and adhesion, and proliferation of monocyte/macrophages, and facilitate Th2-polarization and regulatory T-cell expansion. 1, 2, 27-29 In our study, patients were severely immunocompromised by the HCT procedure and ongoing treatment with immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that older persons treated with statins had an increased risk of herpes zoster infections compared to those not treated with statins. 26 Statins have been shown to inhibit inflammatory chemokine expression, leukocyte migration and adhesion, and proliferation of monocyte/macrophages, and facilitate Th2-polarization and regulatory T-cell expansion. 1, 2, 27-29 In our study, patients were severely immunocompromised by the HCT procedure and ongoing treatment with immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to myopathies, a statin trial should collect data on adverse events related to immunosuppression and insulin resistance, 5860 which may include incident infectious diseases, second primary cancers, changes in fasting insulin levels from baseline, and failure of glucose tolerance tests.…”
Section: A Clinical Trial Of Adjuvant Breast Cancer Therapy With Statmentioning
confidence: 99%
“…Our study offers the first comprehensive analysis of the effect of statins on chronic gammaherpesvirus infection, providing a potential insight into the modification of chronic herpesvirus infections in a significant number of individuals treated with statins. In spite of the prevalent use of statins, the status of herpesvirus activity in statintreated individuals has not been assessed, with the exception of a single study that found a small increase in the incidence of zoster in statin users (41). Importantly, markers of inflammation/immune activity were not taken into account in this study.…”
Section: Discussionmentioning
confidence: 99%